Increased risk of melanoma in C9ORF72 repeat expansion carriers: A case–control study. Issue 3 (27th December 2018) - Tábuas‐Pereira, Miguel; Almendra, Luciano; Almeida, Maria Rosário; Durães, João; Pinho, André; Matos, Anabela; Negrão, Luis; Geraldo, Argemiro; Santana, Isabel
ABSTRACT: Introduction : Amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration (FTLD) are considered part of the same pathological spectrum. There is an increased risk of ALS in patients who have had melanoma. The risk of FTLD in melanoma (or cancer) patients is unknown. We aimed to study if C9ORF72 expansion is linked to a higher prevalence of melanoma. Methods : We selected patients with a diagnosis in the ALS‐FTLD spectrum who were tested for pathogenic mutations. Medical history was reviewed, to identify those with pathologically documented melanomas. Results : We included 189 patients. Sixty‐two had identified pathogenic mutations (39 C9ORF72 ). C9ORF72 carriers had a significantly higher risk of melanoma (odds ratio = 24.709; P < 0.007). There was no association with phenotype. Conclusions : These findings suggest that patients with a history of melanoma may have an increased probability of carrying a C9ORF72 repeat expansion. ALS or FTLD carriers of C9ORF72 should undergo surveillance for skin changes. Muscle Nerve 59 :362–365, 2019